2018
DOI: 10.1016/j.jsams.2017.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Head impact exposure from match participation in women’s rugby league over one season of domestic competition

Abstract: Our cohort of 21 female rugby league athletes were exposed to repetitive sub-concussive head impact exposure with an average of 14 impacts per-player per-match. Forwards were exposed to more impacts per-match than backs and these impacts were of higher magnitude. Most impacts occurred on the side of the head and were sustained during the second half of the game. Clinicians, coaches and players should be aware of the rates and magnitude of head impacts in female rugby league athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 47 publications
0
38
0
Order By: Relevance
“…It has been reported that junior rugby league players [22] recorded a mean of 13 impacts per-player permatch, resulting in a median PLA(g) and PRA(rad/s 2 ) of 16g and 2,773 rad/s 2 . This was similar for senior female amateur rugby league players [24] with a mean of 14 impacts per-player per-match resulting in median PLA(g) and PRA(rad/s 2 ) of 15g and 2,886 rad/s 2 . Senior amateur male rugby league players [23] recorded a higher number of impacts with a mean of 52 impacts per-player per-match resulting in a median PLA(g) and PRA(rad/s 2 ) of 14g and 3,181 rad/s 2 .…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…It has been reported that junior rugby league players [22] recorded a mean of 13 impacts per-player permatch, resulting in a median PLA(g) and PRA(rad/s 2 ) of 16g and 2,773 rad/s 2 . This was similar for senior female amateur rugby league players [24] with a mean of 14 impacts per-player per-match resulting in median PLA(g) and PRA(rad/s 2 ) of 15g and 2,886 rad/s 2 . Senior amateur male rugby league players [23] recorded a higher number of impacts with a mean of 52 impacts per-player per-match resulting in a median PLA(g) and PRA(rad/s 2 ) of 14g and 3,181 rad/s 2 .…”
Section: Introductionmentioning
confidence: 59%
“…To better understand concussive injuries, head impact biomechanics have been extensively studied in a variety of sporting environments such as American football [11][12][13][14], soccer [15,16], ice hockey [17,18], lacrosse [19], Australian rules football [20], rugby union [21] and rugby league [22][23][24]. The studies reporting on head impact biomechanics in rugby league have been undertaken at junior [22], senior amateur male [23] and senior amateur female [24], levels of participation. It has been reported that junior rugby league players [22] recorded a mean of 13 impacts per-player permatch, resulting in a median PLA(g) and PRA(rad/s 2 ) of 16g and 2,773 rad/s 2 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations